Structural properties of superior design solutions of steel buildings associated with BRBs. (December 2021) - Takagi, Jiro; Ohsaki, Makoto; Cao, Yongsheng
Abstract: A design algorithm is proposed for rational seismic design solutions of steel buildings associated with buckling restrained braces (BRB). The strengths and locations of BRBs in addition to the section sizes of structural members are considered as discrete design variables. The steel volume including BRBs is minimized as an objective function under various practical design constraints. A seven-story office building is examined for application in two different types of structural systems, i.e. one mainly consisting of lateral frames and the other with limited utilization of lateral frames typically in perimeter separately from gravity frames. The derived solutions, defined as superior design solutions (SDSs), satisfy serviceability and limit-state constraints, taking into consideration the seismic energy dissipation effect of BRBs using the calculation of resistance and limit-state method. Their rationale is validated with response history analysis. Furthermore, the influences in SDSs by the seismic demand levels and elastic member constraint are investigated. The structural characteristics of SDSs associated with BRBs are objectively evaluated using the proposed design algorithm.